Stosunek Kościoła katolickiego do żydów w czasie pontyfikatu Grzegorza IX (1227-1241). Analiza problemu na podstawie C. 1-19, X, V, 6 - Mrozek, Kinga Anna (Studia Europaea Gnesnensia, 2016)
The chief purpose of the article is to show the position of the Catholic Church towards Jews, as manifested in a selected fragment of Decretales of Gregory IX. Medieval canon law regulated the relations between Christian and Jews in the domains of cult and everyday life. The 19 canons which the relevant fragment comprises were assigned to three categories: laws relating to cult, laws concerning economic issues, and laws providing for the protection of Jews.